(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
B. F. Skinner described in Walden two a fictional community capable of promoting the happiness of its members through cultural design that uses the art among its resources. Walden two is then a privileged work to investigate artistic behavior in Radical Behaviorism. The aim of this theoretical research is to present a systematization about art in Walden two. Excerpts from the book containing key words associated with artistic productions were identified and registered, producing information about: the characteristics of artistic productions, the descriptive variables of artist and audience behavior, and the social function of art. As a kind of social control, the art needs to be considered in ethical-political discussions about cultural design.